Dinâmica do fogo na região Matopiba e sua relação com as mudanças de uso e cobertura - Figueiredo, Raiânnata Machado (2023)
Fire is an ecological process directly influenced by climatic, biological and human factors. Although this phenomenon is recurrent in the Brazilian Cerrado, anthropic alterations have been causing significant changes in its dynamics. Specifically, the MATOPIBA region, inserted in the states of Maranhão, Tocantins, Piauí and Bahia, is one of the main areas within this biome where several land use changes have occurred, since it is considered the last agricultural frontier in the country. These changes are an extremely determinant factor for the occurrence of fire, since they alter the fuel loads and ignition rates. Based on this, the objective of this dissertation was to map the theoretical and empirical knowledge about the relationship between fire and land use change. The first article identified, from searches in the SCOPUS database, articles that investigated the relationship between land use and fire, and from this the main methodological trends within this thematic area were analyzed. The results point to a growth in the number of published articles, with emphasis on the period from 2014 to 2022. It was observed a large number of authors involved in this research, especially the author Shimabukuro, who has the largest number of documents. The countries that published the most were the United States and Brazil. Furthermore, the evolution of terms and key words allowed the analysis of the methodological evolution of these studies. The second article sought to analyze within MATOBIBA, the spatial patterns of the landscape through landscape metrics, the pattern of fire from burn scars and correlate the frequency of burning with areas of transition from natural vegetation to agriculture and cattle ranching, using data from the MapBiomas project, and from this to understand the relationship between fire and changes in land use in the region. As a result it was possible to observe that the main land use transition was the loss of natural vegetation in detriment of the implantation of agriculture and cattle ranching areas, moreover, there is a tendency of fragmentation of the savannah areas, while the agricultural areas are becoming larger and more homogeneous. Savanna areas are also those with the highest frequency of burning. In terms of local correlation, fire is related to land use change predominantly in the west of the MATOPIBA region and in the state of Bahia.